Chia: From Tribute to Super Food - Fonseca González, Vanessa (2017)
This chapter uses world-systems analysis to explain how Chia production evolved from constituting a staple food in the Aztec "world empire" to become integrated in the world-economy system. The first section explains its use and distribution in pre-Columbian times. It highlights its role in the economic system and its articulation within the religious and productive sectors of the Aztec Empire. A second section reviews current chia production and exports mainly in Latin America, in order to map major producers, distributors, mergers, trends and local politics influencing its trade. The analysis explains how chia production and distribution processes dramatically changed in the last 20 years due to different regional factors and increasing global demand for the crop. Finally it assess positioning and branding strategies for chia-based products in key markets worldwide. This chapter reviews how marketing strategies reinvent and brand chia as superfood in late capitalism, when nostalgia and cultural re-signification are central to consumption practices